Ultrasonic Spectroscopy for Characterization of Glycerol and Water Mixtures - Camargo, Gabrielle Ceola [UNESP]; De Souza, Julio Cesar Eduardo [UNESP]; De Souza Alves, Marcelo Ferreira; Tiago, Marcelo Moreira; Elvira, Luis; Higuti, Ricardo Tokio [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2024)
The measurement of liquid properties by ultrasound is widely used in the control of industrial processes, allowing the measurement of acoustic parameters such as propagation velocity and attenuation as a function of frequency and temperature, benefiting from its non-invasive and non-destructive nature. Glycerol is a cheap, easy handling and widely used material, and could be used as a reference liquid in ultrasonic experiments. Due to the lack of experimental results in the literature, in this work, propagation velocity and attenuation of glycerol and water mixtures are measured as a function of frequency and concentration, using a wideband spectrometer. A preliminary analysis of the effect of electronic gain is made, showing its influence on the measured acoustic parameters.
Keywords: Attenuation; Glycerol; Ultrasonic spectroscopy; Velocity